Kritik Sastra Masa Andalusia: Faktor Pengaruh Kemunculan, Tren, dan Kritikus - Husain Miftahul Rizqi (Pascasarjana IAIN Sultan Amai Gorontalo, 2023)
This study aims to describe the factors that influenced the emergence of Arabic literary criticism during the Andalusian period, the trend of literary criticism in the Andalusian era, and the figures of critics in the Andalusian period. This type of research is qualitative research. The method used in this study is library research. The results of this study are among the factors that influenced the emergence of Andalusian literary criticism the rivalry of Eastern people with Andalusian populations, rivalry between fellow literati, criticism sourced from Eastern people, and Arab and Islamic tendencies. The trend of Andalusian literary criticism is still similar to criticism in the East. The Andalusian forms of criticism are language criticism and correction of poetry texts, text analysis and criticism of meaning, comparative literature, manhaji criticism: defense of Andalusian literature, moral criticism: poetry and religion, interpretation of emotions of literary works and their criticism. Various opinions about the man who pioneered literary criticism in Andalusia. The first opinion was pioneered by 'Uthman bin Rabi'ah and 'Ubādah bin Ma' Al-Sama'. Second was Qāsim ibn Nuṣair. Other opinions were Ibn Shahīd and Ibn Ḥazm and were followed by other critics.